Centralization in Headquarters–Subsidiary Relationships - Gates, Stephen R.; Egelhoff, William G. (Journal of International Business Studies, 1986)
Research to date on centralization in MNCs has produced many inconsistent findings. The present study attempts to add clarity to the situation by re-testing many of the existing hypotheses with data from a recent study of centralization in 50 large US, UK and European MNCs. It examines how the degree of centralization inherent in the headquarters-foreign subsidiary relationship varies in response to a variety of company-wide and subsidiary level conditions. The influence of company-wide conditions on centralization appears to be much clearer than the influence of subsidiary-level conditions. The study also identifies several new contingency patterns that appear to be at work in MNCs today.